Influence Of Insructional Media On Teaching And Learning Of Economics In Senior Secondary Schools In Jalingo Metropolis, Taraba State - AUN Thompson Toryuha; Ayeni Atinuke; Ajala Toluwanimi Mcdaniel; Adaaku Judith Mbakeren; Awe Akofe; Salawu Yusuf (Indonesian Journal Publisher, 2022)
The study examined influence of instructional media on teaching and learning of Economics in senior secondary schools in Jalingo metropolis, Taraba State. The study sought the level of availability of instructional media, its usage, by Economics teachers, its influence on teachers and students. The population for the study was 10 SS2 and SS3 Economics students and two teachers from 28 schools. 336 students and teachers; 280 students and 56 teachers were drawn from selected schools. Two researcher designed questionnaire containing 28 items were used to gather data. Descriptive statistics was used to answer research questions one to four while inferential statistics (t-test) was used for the hypotheses. It was revealed that, board and textbooks are often used in teaching and learning of Economics, there is no significant difference in male and female teachers’ perception on the availability of instructional media teaching and learning of Economics in Jalingo metropolis, Taraba State.